Back to School : Pathways for Reengagement of Out-of-School Youth in Education - Rajasekaran, Subhashini (World Bank, Washington, DC, 2019)
Back to School: Pathways for Reengagement of Out-of-School Youth in Education focuses on a social and global problem: 200 million adolescents and youth are out of school, live in adverse life circumstances, and face multiple disadvantages. It analyzes the available evidence for what works, how, and why for reengaging and retaining these young people in education. The study further explores for whom and in what contexts the identified interventions can be effective, considering variations in both individual and contextual characteristics of the targeted youth. This literature review and synthesized findings can be useful to build a broad theory of change with the aim of guiding local policy and programming for designing contextualized interventions for education reengagement.